The Validation of the Information Systems Success Model: LMS Integration during Covid-19 - Miftahuddin Miftahuddin; Lantip Diat Prasojo; Awanis Akalili (Universitas Jambi, Indonesia, 2021)
This study adapted DeLone & McLean information system success model (D&M IS success model) regarding the implementation of learning management system (LMS) during Covid-19. Six variables are included; system quality, information quality, service quality, system usage, user satisfaction, and net benefits with 23 initial items. A total of 279 undergraduate students from a public university in Indonesia participated in this study. The factor structure of the instrument was investigated using a survey design. The survey data were calculated using exploratory factor analysis (EFA) and confirmatory factor analysis (CFA). Six variables emerged from the EFA methods, establishing a valid and reliable model; a few items were eliminated due to cross-loading. The suggested model was successfully mapped as a consequence of the results. The CFA confirmed that the instrument was suitable for the Indonesian setting. The findings led to the development of 19 reliable and valid items. The measured scale has psychometric qualities, allowing for future research with a tool to capture D & M IS success model technology integration.